2018
DOI: 10.1088/1742-6596/1040/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chemistry teaching problems of a prospective teacher: A case study on chemistry teaching

Abstract: Abstract. This study was aimed at identifying chemistry teaching problems of a prospective teacher viewed from the conceptual change model on colloid topic. The study was conducted in one class of one senior high school in Buleleng regency, Bali. The study was a qualitative research of case study type. A number of students in the class were 27 people. The study was done in an academic year of 2013/2014 on the even semester. Methods of the study were observation and interview. The results of the study showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Micro learning can reduce cost-efficiency on knowledge transfer in a project-based organization [7], improve intrinsic motivation [10]. However, a strong appreciation of short duration micro learning for mobile learning can compartmentalize knowledge entities and decline meaningful learning [11][12][13][14][15] for strong interconnected conceptual understanding. Meso learning will minimize such problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro learning can reduce cost-efficiency on knowledge transfer in a project-based organization [7], improve intrinsic motivation [10]. However, a strong appreciation of short duration micro learning for mobile learning can compartmentalize knowledge entities and decline meaningful learning [11][12][13][14][15] for strong interconnected conceptual understanding. Meso learning will minimize such problems.…”
Section: Introductionmentioning
confidence: 99%
“…PPT has important media characteristics for science learning presentations. The development of a PPT prototype of science learning with a problem-based learning model follows the basic model of media development by Luther [17] and with support of alpha and beta testing [15] to its created PPT unit samples. Video segments and worksheet documents which need rather big memory would be placed such in the available google document storage and accessed via hyperlink.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, The Trends of the International Mathematics and Science Study (TIMSS) conducted by the International Association for the Evaluation of Educational Achievement (IEA) in 2011 showed that Indonesian students have a score of 397, below the average of 500. In chemistry learning, students still experience many problems such as being unable to explain chemical phenomena [9,10] and misconceptions [11,12]. This proves that students' scientific knowledge is still limited when given explicit and clear evidence and has not been able to form an explanation based on existing evidence and arguments [13].…”
Section: Introductionmentioning
confidence: 99%